MPCC: strongly stable C-stationary points when the number of active constraints is n + 1. (3rd May 2020) - Hernández Escobar, Daniel; Rückmann, Jan-J.
Abstract : We consider the class of mathematical problems with complementarity constraints (MPCC) and apply Kojima's concept of strongly stable stationary points (originally introduced for a standard optimization problem) to C-stationary points of MPCC under certain assumptions. This concept refers to local existence and uniqueness of a stationary point for each sufficiently small perturbed problem. Assuming that the number of active constraints is n +1 and an appropriate constraint qualification holds at the considered point, the goal of this paper is twofold: For MPCC we will present necessary conditions for strong stability as well as equivalent algebraic characterizations for this topological concept.